Implementasi Peraturan Menteri Agama Tentang Pendidikan Agama Islam Pada Sekolah Dalam Kinerja Pengawas Pendidikan Agama Islam - Manalu, Sahdin Boang; Kadir, Abdul; Siregar, Nina Siti Salmaniah (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
This study aims to analyze the Implementation of the Minister of Religion Regulation of the Republic of Indonesia No 02 of 2012 concerning Madrasah Supervisors and Islamic Religious Education Supervisors at Subulussalam City Junior High School, and to analyze the performance of Islamic Religious Education supervisors in Subulussalam Municipality Middle School. Research informants were selected by purposive sampling. Data collection techniques used through interviews and observation. Data Analysis Techniques used in this study are qualitative data analysis techniques. The results showed that the implementation of RI Minister of Religion Regulation No. 02 of 2012 in terms of communication and bureaucratic structure has been successfully implemented at the Subulussalam Ministry of Religion, but has not been fully successful in terms of resources and disposition. Implementation of RI Minister of Religion Regulation No. 02 of 2012 often experiences obstacles in the field because the conditions faced are less supportive in its implementation so that further policies can become less in line with the regulations implemented. Availability of funds for the implementation of supervision of Islamic Education is still relatively low. Islamic Education Supervisors are also less active in organization, especially supervisory professional organizations, and are less committed to carrying out supervisory duties. The performance of Islamic Education supervisors has increased in terms of the preparation of supervision and reporting programs for the implementation of supervision, but the supervisory performance of Islamic Education has not succeeded in increasing in terms of implementing supervision.